POPULATION DYNAMICS OF PENAEID PRAWN PENAEUS MERGUIENSIS OFF MUMBAI COAST - BHADRA, SUMAN; BIRADAR, R. S. (Journal of Indian Fisheries Association, 2015)
Stock dynamics of Penaeus merguiensis was studied using lengthcomposition data collected seperately for males and females during the period1995-1998, at New Ferry Warf landing, centre in Greater Mumbai. Food andfeeding, sex ratio, facundity and length-weight relationships were worked outon a representative sub-sample. Asymptotic length (Loo) and growth coefficient(K) were estimated to be 220 mm and 1.80 per annum respectively for males.These parameters were respectively 281 mm and 1. 72 per annum in the case offmnales. The instantaneous rate of total mortality coefficient (Z) was found tobe 9.79 and 7.44 per annum for males and females respectively. The annualnatural mortality coefficient (M) was estimated to be 2.80 for males and 2.60for females. As the exploitation ratio exceeded 0.5 in the case of both the malesand females, the study suggests the necessity for reduction in fishing pressurein order to achieve Maximum Sustainable Yield (MSY).Keywords - Banana Shrimp, mortality, Stock assessment, MSY.